Evolution of the Earth's Polar Outflow From Mid‐Archean to Present. Issue 8 (3rd August 2020) - Kislyakova, K. G.; Johnstone, C. P.; Scherf, M.; Holmström, M.; Alexeev, I. I.; Lammer, H.; Khodachenko, M. L.; Güdel, M.
Abstract: The development of habitable conditions on Earth is tightly connected to the evolution of its atmosphere, which is strongly influenced by atmospheric escape. We investigate the evolution of the polar ion outflow from the open field line bundle, which is the dominant escape mechanism for the modern Earth. We perform Direct Simulation Monte Carlo (DSMC) simulations and estimate the upper limits on escape rates from the Earth's open field line bundle starting from 3 gigayears ago (Ga) to present assuming the present‐day composition of the atmosphere. We perform two additional simulations with lower mixing ratios of oxygen of 1% and 15% to account for the conditions shortly after the Great Oxydation Event (GOE). We estimate the maximum loss rates due to polar outflow 3 gigayears ago of 3.3×10 27 s −1 and 2.4×10 27 s −1 for oxygen and nitrogen, respectively. The total integrated mass loss equals to 39% and 10% of the modern atmosphere's mass, for oxygen and nitrogen, respectively. According to our results, the main factors that governed the polar outflow in the considered time period are the evolution of the XUV radiation of the Sun and the atmosphere's composition. The evolution of the Earth's magnetic field plays a less important role. We conclude that although the atmosphere with the present‐day composition can survive the escape due to polar outflow, a higher level of CO2 between 3.0 and 2.0 Ga was likely necessary to reduce the escape. Key Points: Polar outflow escape of the nitrogen ions 3 gigayears ago increases by 2 orders of magnitude compared to its present value Polar outflow of oxygen ions from the Earth's open field line bundle varies greatly depending on the oxygen mixing ratio Polar outflow is governed primarily by the evolution of the solar short‐wavelength radiation and the atmosphere's composition